Information technology risk management for water quality monitoring IoT infrastructure: a case study at Tasik Chini Unesco Biosphere Reserve - Mohamad Shanudin Zakaria,; Ahmad Tarmizi Abdul Ghani,; Muhamad Shukri Yahya,; Siti Narimah Jamali, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Due to its rich and diverse biodiversity of flora and fauna, Tasik Chini, a UNESCO Bisosphere Reserve, is a national heritage that must be preserved and protected. Ensuring healthy water quality here is vital for the survival of the ecosystem. Water quality was constantly being monitored through the use of a network of sensors and telemetry system that collect parameters to determine Water Quality Index since 2004. However, two events have rendered the setup to be inadequate: the economic activities around the lake and the big flood of 2014. Both events has proven that the IoT infrastructure at Tasik Chini is inadequate to mitigate major disaster. The risk of both natural and man-made disasters happening always increased yearly and has a huge impact on water quality monitoring as well as the dissemination and sharing of data and results. A proper management plan to mitigate these risks is needed. The purpose of this paper is to highlight a successful research methodology that has been proposed and done in monitoring and improving Tasik Chini water quality. First, needs analysis were carried out through face-to-face interaction with researchers and the indigenous community living within the vicinity of the lake. Historical water quality data were also compiled and analyzed to validate the degradation of water quality over the years. Second, a proper risk registers and risk respond plan was developed. The current telemetry and network of sensors were reengineered by introducing new online tools for sharing and disseminating of water quality data to more diverse stakeholders. Cloud and 4G services are now the integral part of monitoring. Third, an early warning system has been developed to complete the setup.